Polimorfismo e expressão de genes de celulose sintase em eucalyptus - Trigueiro, Elaine Lima (2007)
Cellulose is one of the most important and the most abundant biopolymer on the planet, playing a key role on the evolutionary history of plants. Important advances have been made in recent years, in particular on the identification of genes and co- expressed genes for the formation of cellulose in the primary and secondary cellular walls of plants. In addition to its biological relevance, cellulose has a great economic importance, not only in Brazil but in the world, especially due to the production of cellulose and paper from Eucalyptus. The high levels of production and competition in the international market are guaranteed by great investments, which are carried through by the forestal sector, in particular by the Genolyptus Project – Brazilian Network for Research on Eucalyptus Genome. This project is the result of a collective effort of companies involved on the production of cellulose and paper and various public research institutions. Their main goal is to identify and characterize genes involved in wood formation with the intent to genetically improve Eucalyptus. Based on this goal, this work was developed with two objectives. The first is doing a preliminary characterization of the cellulose synthase gene in Eucalyptus, which is associated with the synthesis of the secondary cellular wall and is orthologous to the gene EgCeA2, of E. grandis. The second objective is to study the linkage disequilibrium in another gene of cellulose synthase, orthologous to the EgCesA3 gene, sampled from a wild population of E. urophylla. Regarding the CesA2 gene, an exonic region with 427bp was sequenced from DNA samples of 12 individuals from different species and geographic regions. The next step was to proceed with an analysis to detect polymorphism which gave an estimate of three SNPs synonymous along the contig, with an estimated π = 0.00212 diversity index. A clone containing the CesA2 gene was identified through a selection from a BAC library generated in the scope of the Genolyptus Project. This clone gives the prospect for the development of a minute characterization of this gene structure in Eucalyptus. Additionally, concerning the CesA3 gene, the sequencing of 32 individuals allowed for the formation of a 770bp contig with a π = 0.00185 diversity index and detection of nine polymorphic loci distributed in intron and exon regions and at the 3’-UTR of the gene. The analysis of the extension of linkage disequilibrium in the CesA3 gene suggests that SNPs tend to be in strong linkage disequilibrium at a distance of approximately 600bp. The knowledge of the position of the SNPs in the genes CesA2 and CesA3 makes possible the use of these markers in future studies of genetic mapping. The lack of non-synonymous SNPs in exon regions ensures that cellulose is in fact a very important polymer for plant survival. Hence its synthesis machinery presents highly conserved characteristics and so mutations in regions with effective transcription tend mostly to be deleterious and therefore would not be fixed. Moreover, the analysis of CesA gene expression in different species of Eucalyptus, was made from two boardings: “Digital Differential Display”, from different libraries of ESTs and microarrays, optimized in the scope of the Genolyptus project. The analysis with data of microarrays showed less sensible in the detention of the distinguishing expression, probably had to the calls “crossed relations”.